2022
DOI: 10.1007/s12518-022-00434-2
|View full text |Cite|
|
Sign up to set email alerts
|

The interrelationship between LST, NDVI, NDBI, and land cover change in a section of Lagos metropolis, Nigeria

Abstract: This article was inadvertently published shortly after the initial submission of correction. There had been a correction in Eq. 3 and Tables 8, 9, 10 when the whole team of authors finalized the corrections. The authors have limited the analysis of variation in LST, NDVI, and NDBI, and their relationship with land cover to the Landsat 8-derived data only (2013, 2016 and 2019). Consequently, year 2002 has been excluded from the initial tables 8, 9, 10, 11. Given here are the corrected equation and tables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…These results are important in terms of showing that vegetation areas decreased according to NDVI and SAVI calculations, water-covered areas decreased according to mNDWI calculations, and built areas increased according to NDBI calculations. The results of the negative and positive relationships of NDVI and NDBI with LST are in parallel with many studies in the literature (Chen & Zhang, 2017;Ranagalage et al, 2017;Malik et al, 2019;Jamei et al, 2019;Shahfahad et al, 2020;Halder et al, 2021;Yamak et al, 2021;Alademomi et al, 2022;Değerli & Çetin, 2022). The negative relationship between SAVI and LST also supports the study results of Akyürek (2020).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…These results are important in terms of showing that vegetation areas decreased according to NDVI and SAVI calculations, water-covered areas decreased according to mNDWI calculations, and built areas increased according to NDBI calculations. The results of the negative and positive relationships of NDVI and NDBI with LST are in parallel with many studies in the literature (Chen & Zhang, 2017;Ranagalage et al, 2017;Malik et al, 2019;Jamei et al, 2019;Shahfahad et al, 2020;Halder et al, 2021;Yamak et al, 2021;Alademomi et al, 2022;Değerli & Çetin, 2022). The negative relationship between SAVI and LST also supports the study results of Akyürek (2020).…”
supporting
confidence: 88%
“…It is estimated that 66% of the world's population will live in urban areas by 2050 (United Nations, 2014). With the rapidly increasing population around the world, the need for new settlements arises, which causes a rapid land use / land cover (LULC) change (Alademomi et al, 2022). These changes and transformations bring serious environmental consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in green space over the years has been revealed. In the light of recent studies, it has been revealed that bare soil areas, rocky areas and built-up areas affect LST in an upward direction, while wet areas and green areas have a decreasing effect on the contrary (Alademomi 2022;Alademomi 2020;Kulsum and Moniruzzaman 2022). ; Ghouri et al 2022;Khalis et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study conducted by Alademomi, Okolie, Daramola, Akinnusi, Adediran, Olanrewaju, Alabi, Salami and Odumosu [10] has tested the relationship among spectral indices such as vegetation index (NDVI), built up index (NDBI), and LST. The results of those studies indicate that NDVI is inversely proportional to LST, while NDBI is directly proportional to LST.…”
Section: Introductionmentioning
confidence: 99%